Divergent roles of the regulatory subunits of class IA PI3K - Kim, Cho-Won; Lee, Junsik M.; Park, Sang Won (Frontiers in Endocrinology, 2024)
The regulatory subunit of phosphatidylinositol 3-kinase (PI3K), known as p85, is a critical component in the insulin signaling pathway. Extensive research has shed light on the diverse roles played by the two isoforms of p85, namely p85α and p85β. The gene pik3r1 encodes p85α and its variants, p55α and p50α, and while pik3r2 encodes p85β. These isoforms exhibit various activities depending on tissue types, nutrient availability, and cellular stoichiometry. Studies involving whole-body or liver-specific deletion of pik3r1 have shown increased insulin sensitivity and improved glucose homeostasis; however, skeletal muscle-specific deletion of p85α displays no significant effects on glucose homeostasis. On the other hand, the lack of whole-body pik3r2 improves insulin sensitivity but does not have a significant impact on glucose tolerance. Notably, liver-specific double knockout of pik3r1 and pik3r2 leads to reduced insulin sensitivity and glucose tolerance. In the context of obesity, upregulation of hepatic p85α or p85β has been shown to improve glucose homeostasis. However, hepatic overexpression of p85α in the absence of p50α and p55α in obese mice results in increased insulin resistance. Moreover, p85α and p85β have distinctive roles in cancer development with p85α acting as a tumor suppressor and p85β promoting tumor progression. In the immune system, p85α facilitates B cell development, while p85β regulates T cell differentiation and maturation. This review provides a comprehensive overview of the distinct functions attributed to p85α and p85β, highlighting their significance in various physiological processes, including insulin signaling, cancer development, and immune system regulation.